2013
DOI: 10.1016/j.geoforum.2013.08.004
|View full text |Cite
|
Sign up to set email alerts
|

Gifts, sustainable consumption and giving up green anxieties at Christmas

Abstract: This paper explores the proposition that gifting is a little recognised yet important practice bound up in the quest for sustainable consumption, which has largely been studied with reference to market rather than gift economies. It draws on gift theories in economic anthropology which explain gifts as engendering social relations of reciprocity and beyond, and shaping social life differently to commodities. Understanding how and why commodities become gifts (and vice versa), we contend, provides a new way of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 20 publications
0
12
0
Order By: Relevance
“…The second cluster of work to be addressed sits at the intersection of material geographies and cultural environmental research, and is most readily associated with Chris Gibson, Lesley Head and colleagues (for example Farbotko & Head, ; Gibson et al., ; Gibson et al., ; Head, Gibson, Gill, Carr, & Waitt, ; Head et al., ; Waitt & Phillips, ) as well as a number of contributions to Ruth Lane and Andrew Gorman‐Murray's () edited collection Material geographies of household sustainability . Starting from the observation that the household is a scale that not only makes sense to policy‐makers as a site of government intervention, but also to the people who live in them; this research explores the relationships, emotions, meanings, materials and practices that are involved in the creation and maintenance of the home.…”
Section: Sustainability Consumption and Everyday Lifementioning
confidence: 99%
“…The second cluster of work to be addressed sits at the intersection of material geographies and cultural environmental research, and is most readily associated with Chris Gibson, Lesley Head and colleagues (for example Farbotko & Head, ; Gibson et al., ; Gibson et al., ; Head, Gibson, Gill, Carr, & Waitt, ; Head et al., ; Waitt & Phillips, ) as well as a number of contributions to Ruth Lane and Andrew Gorman‐Murray's () edited collection Material geographies of household sustainability . Starting from the observation that the household is a scale that not only makes sense to policy‐makers as a site of government intervention, but also to the people who live in them; this research explores the relationships, emotions, meanings, materials and practices that are involved in the creation and maintenance of the home.…”
Section: Sustainability Consumption and Everyday Lifementioning
confidence: 99%
“…Regarding SRC behaviours, literature provides few studies that have examined the impact of atmospheric variables upon people's socially responsible behaviour. To our knowledge, only Farbotko and Head () have conducted a longitudinal study of 15 environmentally engaged households and have shown that environmental concerns are not expressed through gifts. Nevertheless, a strong feature of the Christmas atmosphere is the tradition of gift exchange.…”
Section: Atmosphericsmentioning
confidence: 99%
“…Past research in consumer behaviour mostly explored SRC for regular purchases, but ignored extraordinary situations, like Christmas. It is important to study Christmas consumption because, in contemporary Western societies these festive occasions have become synonymous with overconsumption (Farbotko & Head, ). For instance, a PwC (2014) study has shown that Irish people who spend US$1,096 on average for Christmas far exceed the English (US$971) and the Americans (US$707).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Birmingham has successfully transferred the European custom of Christmas market (Bloom…eld 2010) 2. Christmas makes a di¤erence, even for green consumers (Farbotko and Head 2013).…”
Section: Appendix -The Supplementary Christmas Report Of the Elvesmentioning
confidence: 99%